The Effect of Green HRM on Employee Green Behavior through Environmental Awareness and Green Innovative Work Behavior - Rianti Setyawasih; Haris Budiyono; Jamalludin Harahab (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The increasing pressure on industrial companies to implement sustainable business practices has strengthened the strategic role of green Human Resource Management (HRM) in promoting environmentally responsible employee behavior and sustainability-oriented workplace innovation. However, empirical studies examining the sequential mechanisms linking green HRM, environmental awareness, green innovative work behavior, and employee green behavior within Indonesia’s manufacturing sector remain limited. This study aims to analyze the effect of green HRM on employee green behavior through environmental awareness and green innovative work behavior as serial mediating variables among automotive manufacturing employees in Karawang. The research employed a quantitative explanatory approach using survey-based data collected from 100 employees selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that green HRM significantly influences environmental awareness and green innovative work behavior. Environmental awareness also significantly affects green innovative work behavior and employee green behavior, while green innovative work behavior significantly influences employee green behavior. Furthermore, environmental awareness and green innovative work behavior sequentially mediate the relationship between green HRM and employee green behavior. These findings contribute to sustainable human resource management literature by integrating sustainability-oriented innovation behavior into the Green HRM framework.